Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.9734/jpri/2021/v33i64b35782
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Association between Clinical Examination and Investigations with Outcome in Cases of Abdominal Malignancy

Abstract: Introduction: Abdominal malignancy is a serious problem in the western world which is presently rising in India due to change in lifestyle. The etiopathogenesis are hereditary, environmental and lifestyle factors. The signs and symptoms vary depending upon the type and stage of cancer. Routine investigations, tumor markers, radiology, endoscopy and biopsy examine patients. There have been advances in chemotherapy, radiotherapy, and palliation but still surgery is curative. Methods: This is a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Contribution of this technique in formulation of further patient management was stressed [19,20,21]. Similar studies were reported by Rashmi S. et al [22], Yeola et al, [23,24]. Few of the related studies were reviewed [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 76%
“…Contribution of this technique in formulation of further patient management was stressed [19,20,21]. Similar studies were reported by Rashmi S. et al [22], Yeola et al, [23,24]. Few of the related studies were reviewed [25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 76%